Development of the Islamic Religious Education Curriculum in Indonesia - Samuji, Samuji; Wahib, Ahmad (STAI MA'ARIF MAGETAN, INDONESIA, 2024)
This study aims to describe the developmentof the Islamic Religion Education (PAI) curriculum in Indonesia, with a focus on the development of the Pre-Independence, oLd Order, New Order, and Reform Era to the Indepenent Curriculums. This research uses the library research method. Data coleection was carried out using documentation study techniques. The result of this study indicate that Islamic Religious Education (PAI) is experiencing dynamics of development in the New Order era to the current reform era, Islamc religious education is experiencing positive developments, it’s just that the curriculum still has to be designed to be compatiblewith the dynamis of the times.